Kajian Hidrologi untuk Mitigasi Longsor di Kawasan Jalan Sisi Lumajang (Sta.58+830 sd 59+930) - Karuru, R.S.; Lioni, C.S.; Mantong, T.M.P.; Ramadhan, B.R.; Payung, F.R. (Tadulako University, 2025)
Watershed (DAS) of a tributary have caused landslides along the access road to the Besuk Koboan road and bridge construction project in Sumberwuluh Village, Candipuro District, Lumajang Regency. The watershed area examined in this study was located on the slope at STA 58+670, and is analyzed to assess surface runoff entering the main road due to the lack of natural reinforcement from vegetation as a result of land use conditions. Identification results indicate that the landslide was caused by erosion (scouring) at the base and foot of the slope; the riverbanks are composed of porous and easily eroded lava deposits from Mount Semeru, as well as water seepage from the cliff. The proposed landslide mitigation con+cept for the river slope includes: Slope reinforcement using piles, Design of a drainage system to manage surface water runoff, Protection of the slope foot from scouring using gabion structures (gabion lay dams) or riprap, Slope crest arrangement to reduce water infiltration, Box culvert cross-section design that takes into account the landslide condition on the slope. Furthermore, regarding the landslide condition affecting the National Road segment Malang–Lumajang at STA 58+830 to 58+930, which was impacted by inadequate existing drainage infrastructure, it is crucial to reconstruct the drainage system based on the analysis and study that has been conducted